Emotional support and its relationship to Emotional intelligence - Atoum, Adnan Yousef; Al-Shoboul, Rasha Ahmed (Advances in Social Sciences Research Journal, 2018)
This study aimed to reveal emotional support from family, teacher, friends, and social medial network among a sample of (732) ninth graders Jordanian students, and to investigate the relationship between emotional support and emotional intelligence. The results of the study showed a high level of emotional support, and revealed that there were significant positive relationships between emotional support (family, teacher, friends, and network) and emotional intelligence. In addition, family and friend emotional support contributed significantly in the variation of emotional intelligence.